From a diagram with input $x(n)$ a summer and three feedback delay taps I get the difference equation...

$$y(n) = x(n)+a_1y(n-1)+a_2y(n-2)+a_3y(n-3)$$

Then I am given values for ai coefficients.

Case1: $a_1=0,a_2=1,a_3=0$

When applying ai values I get

$y(n) = x(n)+y(n-2)$


$$Y(z) = X(z)+Y(z)z^{-2}$$

$$Y(z)-Y(z)z^{-2} = X(z)$$

$$Y(z)(1-z^{-2}) = X(z)$$

$$\frac{Y(z)}{X(z)} = \frac{1}{1-z^{-2}}$$

I’m just wondering if this is correct. If not, I wouldn’t like to be given the answers I would just like to know what I’m doing wrong.

Thanks in advance to anyone who may help.


1 Answer 1


Yes, that's correct.

Tip: If you write the difference equation in "standard" from

$$ \sum_i a_i y[n-i] = \sum_i b_i x[n-i] $$

it has a one to one correspondence with the z-transform.

$$H(z) = \frac{\sum_i b_i z^{-i}}{\sum_i a_i z^{-i}} $$

In your example $$y[n]-a_2 \cdot y[n-2] = x[n]$$ yields $$H(z) = \frac{1}{1-a_2 \cdot z^{-2}}$$

  • $\begingroup$ Thanks for the edit lennon310 I will pay more attention to my formatting going forward. $\endgroup$
    – New2Dsp
    Aug 16, 2021 at 12:43
  • $\begingroup$ Thanks for the clarification Hilmar $\endgroup$
    – New2Dsp
    Aug 16, 2021 at 12:44

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.